PROFESSIONAL COMPETENCIES OF MANAGERS IN THE SPORTS AND RECREATION INDUSTRY IN THE UNITED STATES OF AMERICA AND EASTERN EUROPE - Tolchieva, Hanna (Public Management and Policy, 2026)
The article examines the current problems of finding and forming professional competencies for managers of the sports and recreation industry using the experience of the United States of America and Eastern Europe as an example. The purpose of the article is to study the model characteristics of the functioning of the sports and recreation industry in the United States of America and Eastern Europe and to substantiate the complex of professional competencies for managers of this sphere. To achieve the set tasks, a set of general scientific research methods was used, in particular, systemic, competency-based, comparative and interdisciplinary approaches to the study of the sports and recreation industry. The following methods were used in the research process: analysis and synthesis of scientific literature, regulatory and program documents; comparative analysis to identify the features of the functioning of the sports and recreation industry in the United States of America and Eastern European countries; generalization and systematization of scientific data to substantiate the complex of professional competencies of managers; theoretical modeling method to determine the model characteristics of the functioning of the sports and recreation industry in the studied regions. The article proposes model characteristics of the functioning of the sports and recreation industry in the United States of America and Eastern Europe and substantiates the most important competencies for managers of the sports and recreation industry.